A biomass-derived polyhydroxyalkanoate biopolymer as safe and environmental-friendly skeleton in highly efficient gel electrolytes for lithium batteries. (1st September 2017) - Dall'Asta, V.; Berbenni, V.; Mustarelli, P.; Ravelli, D.; Samorì, C.; Quartarone, E.
Highlights: We report on biomass derived PHA biopolymer as eco-friendly skeleton in GPE for LiB. The gel was biodegradable, stable and showed excellent functional performances. Biopolymer: Successful approach for green and safe electrolyte for sustainable LiBs. Abstract: The massive use of lithium batteries in industries, such as automotive and electrical network accumulation, requires the development of safer electrolytes, economic and possibly made from renewable resources using eco-friendly processes. In this work, we reported the synthesis and the physico-chemical and functional characterization of a polymer gel electrolyte (GPE) based on a skeleton of polyhydroxyalkanoate obtained from biomass by means of an easy and environmentally friendly chemical process. The GPE has an ionic conductivity of 0.8 mS cm −1 at room temperature, is thermally stable up to over 100 °C and is not flammable. The electrochemical stability window is higher than 5 V. The cell Li/GPE/LiFePO4 shows specific capacity of 100 mAhg −1 at 3C with 100% coulombic efficiency. These results demonstrate that the GPE based on polyhydroxyalkanoate is very promising for use in lithium batteries of high power density.